The effect of principal’s leadership, school climate and teaching-learning process on economics learning outcomes - Nurhasanah Nurhasanah; Syamsul Amar; Idris Idris (Fakultas Ilmu Pendidikan UNP)
This research was aimed to find and anlyze: (1) the effect of principal’s leadership and school climate on economics learning outcomes of students at state senior high schools (hereinafter SMA N) in Padang City and (2) the effect of principal’s leadership, school climate and teaching-learning process on economics learning outcomes of students at SMA N in Padang City. This study belongs to descriptive causal research design. Research population were 62 economics teachers and the sample are 32 economics teachers. Result of this research found that, (1) Principal’s leadership and school climate had a significant effect on economics learning outcomes of students at SMA N in Padang City. (2) Principal’s leadership, school climate and teaching-learning process significantly affect economics learning outcomes of students at SMA N in Padang City.